The Life and Letters of Charles Darwin, Volume 1 Including an Autobiographical Chapter - Darwin, Charles 1809-1882 (Cambridge library collection. Darwin, Evolution and Genetics, 1887)
This book, the first of three-volumes detailing the life of Charles Darwin, published five years after his death, was edited by his son Francis, who was his father's collaborator in experiments in botany and who after his death took on the responsibility of overseeing the publication of his remaining manuscript works and letters. In the preface to the first volume, Francis Darwin explains his editorial principles: 'In choosing letters for publication I have been largely guided by the wish to illustrate my father's personal character. But his life was so essentially one of work, that a history of the man could not be written without following closely the career of the author.' Among the family history, anecdotes and reminiscences of scientific colleagues is a short autobiographical essay which Charles Darwin wrote for his children and grandchildren, rather than for publication. This account of Darwin the man has never been bettered